INTESTINAL ROTATION AND FIXATION ABNORMALITIES IN CHILDREN - CLINICAL COURSE, DIAGNOSIS AND TREATMENT APPROACHES - A.I. Lenyushkin; I.N. Khvorostov ("Paediatrician" Publishers LLC, 2007)
The article elucidates current opinion on embryogenesis and anatomical variants of intestinal rotation and fixation abnormalities (IRFA) in children describing signs and symptoms, clinical course and methods of diagnostics in 83 patients (age 0-9 years old). The authors emphasize characteristic features of manifestation and clinical course in connection with anatomical variant and age and consider possible treatment approaches.Key words: children, intestine, abnormal rotation and fixation.